Witness Testimony in the Law of Evidence: A Comparative Analysis of Fuqaha Perspectives and Civil Law - Rahmatul Qadri; Andi Huzaifa; Abdul Halim Talli; Asni (International Journal of Social Science and Religion (IJSSR), 2026)
The determination of the evidentiary value of witness testimony depends not only on the facts presented before the court but also on the legal paradigm through which juridical truth is constructed. This study examines the evidentiary value of witness testimony from the perspectives of fuqaha and civil law to explain the epistemological foundations underlying their different approaches. Employing normative legal research with conceptual, statutory, and comparative approaches, this study finds that although both legal traditions recognize witness testimony as an essential means of proof, they adopt different standards for assessing its probative value. Islamic jurisprudence emphasizes the witness's moral credibility (ʿadālah) and legal qualifications, whereas civil law primarily relies on procedural legality and judicial evaluation. These differences demonstrate that the evidentiary value of witness testimony is fundamentally shaped by distinct epistemological conceptions of juridical truth. Accordingly, this study advances an epistemological perspective that enriches comparative scholarship on the law of evidence.